Pengaruh Interaction Dan Price Discount Di Live Streaming Instagram Terhadap Purchase Intention Produk Thrift Dimediasi Oleh Trust - Prabowo, Fahmi Hadi; Kumalasari, R. Amalina Dewi (eProceedings of Management, 2024)
Consumer trust is a crucial factor in the formation of purchase intention, but not many studies have examined theinfluence of interaction and price discounts on thrift product trust and consumer purchase intention on the Instagramlive streaming platform. This study aims to investigate the influence of interaction and price discounts on thrift producttrust and consumer purchase intention in Instagram live streaming. In the context of online shopping, consumer trustplays an important role in shaping purchase intentions. The research method used is quantitative with non probabilitysampling data collection techniques with 193 respondents. The data analysis technique uses Micosoft Excel andSmartPLS software. The results of this study will be explained through descriptive analysis and Partial Least Square(PLS) with SmartPLS 3 & 4 software. The conclusion that can be drawn from the research results is that eachinteraction and price discount has a direct influence on trust and purchase intention of thrift products via Instagramlive streaming. Apart from that, trust can also mediate well the respective effects of interaction and price discount onpurchase intention. Thus, marketing strategies that focus on good interaction and providing price discounts canincrease consumer confidence and encourage purchasing interest in purchasing thrift products online via Instagramlive streaming shopping..Keywords-interaction, price discounts, purchase intention, trust